Anemia in Heart Failure Patients. (25th March 2012) - Alexandrakis, Michael G.; Tsirakis, George
Abstract : Heart failure is a very common disease, with severe morbidity and mortality, and a frequent reason of hospitalization. Anemia and a concurrent renal impairment are two major risk factors contributing to the severity of the outcome and consist of the cardio renal anemia syndrome. Anemia in heart failure is complex and multifactorial. Hemodilution, absolute or functional iron deficiency, activation of the inflammatory cascade, and impaired erythropoietin production and activity are some pathophysiological mechanisms involved in anemia of the heart failure. Furthermore other concomitant causes of anemia, such as myelodysplastic syndrome and chemotherapy, may worsen the outcome. Based on the pathophysiology of cardiac anemia, there are several therapeutic options that may improve hemoglobin levels, tissues' oxygenation, and probably the outcome. These include administration of iron, erythropoiesis-stimulating agents, and blood transfusions but still the evidence provided for their use remains limited.